Olympic athletes should get priority access to coronavirus vaccines, IOC's Dick Pound says (CBC, 2021)
In order to safeguard the Tokyo Olympics, athletes must be given priority access to the coronavirus vaccine, says prominent International Olympic Committee member Dick Pound.